Polymer Materials in Environmental Chemistry - Padil, Vinod V.T (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book entitled "Polymer Materials in Environmental Chemistry" focuses on functionalized natural/synthetic polymeric materials and their preparation, characterization, and multidimensional applications. This book extensively appraises the research papers on the latest developments of the functionalized natural/synthetic polymers, such as the effect of functionalized polymeric additives on the degradation of aliphatic polyesters, development of nanoparticle functionalized bio-based or composite polymeric structures, water or wastewater purification, natural fibers or clay-based hybrid polymers and their applications, environmental remediation of antibiotics and dyes using polymer-based nanofibers, bio-based polymeric conjugate for the synthesis of bimetallic nanoparticles and their catalytic degradation of ecological pollutant, polymeric-grafted membranes based on ethyl cellulose for gas separation, and polyamide-laccase nanofiber membranes for the degradation of organic and antibiotics from water. Additionally, the book envisages the reviews on recent developments in the techniques and visualization of biopolymer structures and their derivatives and fabrication and characterization of polymeric nanofibers via multidimensional electrospinning techniques and their appliances in environmental pollutant removal.